Eigenvalues and Eigenvectors of a Matrix Dependent on Several Parameters (Journal of Computational Mathematics, 2021)
This paper describes a method for investigating the analyticity and for obtaining perturbation expansions of eigenvalues and eigenvectors of a matrix dependent on several parameters. Some of results of this paper provide justification of the applications of the Newton method for inverse matrix eigenvalue problems.